(untitled) (Práxis Educativa, 2022)
This article presents part of a study that aimed to identify ethnomathematic narratives and practices produced by workers from the Carnival of Florianópolis, state of Santa Catarina, Brazil, in order to recognize samba schools as educational spaces, where (mathematical) practices and learning are developed. The study included theoretical, historical and documentary research, as well as fieldwork that focused on observing, analyzing and describing carefully and respectfully the social reality of the components, using conversations, semi-structured interviews and audiovisual recordings. In this text, the carnival shed of floats of the association Os Protegidos da Princesa was analyzed. Educational processes through curiosity and observation are highlighted, in addition to the production of materials and techniques to solve the demands of the construction of Carnival floats. Keyword: Ethnomathematics. Samba schools. Ethnic-racial relations.